JHDM1B expression regulates ribosome biogenesis and cancer cell growth in a p53 dependent manner. Issue 5 (10th October 2014) - Penzo, Marianna; Casoli, Lucia; Pollutri, Daniela; Sicuro, Laura; Ceccarelli, Claudio; Santini, Donatella; Taffurelli, Mario; Govoni, Marzia; Brina, Daniela; Trerè, Davide; Montanaro, Lorenzo
<x xml:space="preserve">Abstract</x> Tumors characterized by an intense ribosome biogenesis often display a more aggressive behavior. Ribosomal RNA (rRNA) synthesis is controlled at several levels, including the epigenetic regulation of the condensation of chromatin portions containing rRNA genes. JHDM1B (Jumonji C histone demethylase 1B) is a histone demethylase able to regulate the accessibility of rRNA genes. In this study, we aimed to define the contribution of JHDM1B expression to the features of breast cancer, a tumor type whose behavior is related to the rate of ribosome biogenesis. We show that, in breast cancer‐derived cell lines, the increase in rRNA transcription that follows JHDM1B knock‐down is mirrored by an augmented cell proliferation only in p53 compromised cells, while p53 competent cells undergo cellular senescence and death. The latter effect appears to be mediated by a p38‐dependent phosphorylation of p53, inducing the expression of p15Ink4b and p21Waf1. In breast cancers, lower JHDM1B expression correlates with an increased size of specifically stained nucleolar organized regions, a morphological parameter directly related to the rate of ribosome biogenesis and with a poorer prognosis. In addition, in tumors lacking the controller function of p53, a lower expression of JHDM1B is associated with an increased tumor size at diagnosis. Altogether, our data indicate that epigenetic activation of rDNA genes induced by JHDM1B depletion is associated with a p53‐dependent growth arrest, but may promote cancer cell growth when p53 is lacking.